Potential of Fig Fruit Ethanol Extract (Ficus carica L.) Against Staphylococcus aureus MRSA and Klebsiella pneumoniae ESBL Bacteria - Enmia Septia Padang; Rini Hafzari; Endang Sulistyarini Gultom (Biology, Medicine, & Natural Product Chemistry, 2025)
Ficus carica L. commonly known as figs originate from West Asia and have bioactive components with antibacterial properties. This study aimed to determine the antibacterial activity of fig ethanol extract in inhibiting the growth of MDR Staphylococcus aureus MRSA and Klebsiella pneumoniae ESBL bacteria, to determine the MIC and MBC values, and the types of compounds contained in fig ethanol extract. The method began with fig extraction using concentrations of 20%, 40%, 60%, 80%, and 100% with 4 repetitions, testing MIC and MBC using the liquid dilution method, TLC-Bioautography test with ethyl acetate: methanol: aquades (7: 2: 1) eluent. The results showed that fig fruit extract had an inhibition zone with an average value of 3.30 mm at a concentration of 100% which was still in the weak category, the MIC value of Staphylococcus aureus MRSA bacteria was a concentration of 100% and Klebsiella pneumoniae ESBL bacteria was a concentration of 80%. The MBC value of MDR bacteria was not obtained because there was still bacterial growth. The results of the TLC-bioautography test of ethanol extract of fig fruit (Ficus carica L.) can inhibit bacterial growth indicated by the presence of a clear zone with an Rf value of 0.5 cm (unidentified), 0.31 cm (Flavonoid), 0.2 cm (Phenol). The compounds that act as antibacterials against Staphylococcus aureus MRSA and Klebsiella pneumoniae ESBL bacteria are the flavonoid and phenol groups.